Absorption and plasma kinetics of collagen tripeptide after peroral or intraperitoneal administration in rats. Issue 12 (2nd December 2015) - Yamamoto, Shoko; Hayasaka, Fumitaka; Deguchi, Kisaburo; Okudera, Toshimitsu; Furusawa, Toshitake; Sakai, Yasuo
Abstract: Collagen tripeptide (CTP) is a collagen-derived compound containing a high concentration of tripeptides with a Gly-X-Y sequence. In this study, the concentrations and metabolites of CTP were monitored in rat plasma after its administration. We performed a quantitative analysis using high-performance liquid chromatography tandem mass spectrometry according to the isotopic dilution method with stable isotopes. We confirmed that the tripeptides Gly-Pro-Hyp, Gly-Pro-Ala, and Gly-Ala-Hyp were transported into the plasma. Dipeptides, which are generated by degradation of the N- or C-terminus of the tripeptides Gly-Pro-Hyp, Gly-Pro-Ala, and Gly-Ala-Hyp, were also present in plasma. The plasma kinetics for peroral and intraperitoneal administration was similar. In addition, tripeptides and dipeptides were detected in no-administration rat blood. The pharmacokinetics were monitored in rats perorally administered with Gly-[ 3 H]Pro-Hyp. Furthermore, CTP was incorporated into tissues including skin, bone, and joint tissue. Thus, administering collagen as tripeptides enables efficient absorption of tripeptides and dipeptides. Graphical abstract: : Plasma kinetics of peptides in the two routes of administration, and autoradiographs after peroral administration of Gly-[ 3 H]Pro-Hyp.